ChemInform Abstract: Salaterpene E, a Eudesmane‐Type Sesquiterpene from Salacia longipes var. camerunensis. Issue 26 (June 2016) - Mba'ning, Brice Mittrant; Ndjakou, Bruno Lenta; Talontsi, Ferdinand Mouafo; Lannang, Alain Meli; Dittrich, Birger; Ngouela, Silvre Augustin; Tsamo, Etienne; Sewald, Norbert; Laatsch, Hartmut
Abstract: isolation and structure elucidation of salaterpene E (I)